آثر التحول للصيرفة الإسلامية على الأداء المالي للمصارف التجارية دراسة تحليلية على المصارف التجارية الليبية العامة باستخدام نموذج PATROL (Comprehensive Journal of Science, 2025)
This study investigates the financial performance of Libyan public commercial banks before and after their conversion to Islamic banking. The PATROL model, approved by the Italian Central Bank, is employed to analyze five key indicators: capital adequacy, profitability, credit risk, regulation, and liquidity. Data from three years before (2010-2012) and three years after (2015-2017) the conversion is analyzed and compared using PATROL.  The study reveals that the conversion to Islamic banking had a negative impact on the financial performance of the banks in the sample. Their overall classification score before the conversion was better than after the conversion, suggesting deficiencies in the transition process and deterioration in credit quality and regulatory compliance. A general classification based on PATROL grades and a preference ranking within the classification are developed for the studied banks.  It is recommended that the Central Bank of Libya adopt the PATROL model for monitoring commercial banks' performance. Additionally, banks should diversify investments and utilize various Islamic finance instruments, not solely relying on Murabaha  .